A New Magnetic levitation System for Pipeline Inspection. (November 2020) - Wang, Ao; Zhang, Yan
Abstract: Through simulation design and simulation calculation, a new magnetic suspension system for pipeline detection is proposed. The system is convenient to carry pipeline detection device and realize the detection of pipeline interior. In this paper, the theoretical principle of the system is discussed, the model is simulated by using the simulation software, and the control method of the system is analyzed theoretically.